2023
DOI: 10.3390/genes14081614
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Global Phylogeny of Mitochondrial N1a, X, and HV2 Haplogroups Based on Rare Mitogenomes from Croatian Isolates

Abstract: Mitochondrial DNA (mtDNA) has been used for decades as a predominant tool in population genetics and as a valuable addition to forensic genetic research, owing to its unique maternal inheritance pattern that enables the tracing of individuals along the maternal lineage across numerous generations. The dynamic interplay between evolutionary forces, primarily genetic drift, bottlenecks, and the founder effect, can exert significant influence on genetic profiles. Consequently, the Adriatic islands have accumulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 121 publications
(157 reference statements)
0
0
0
Order By: Relevance
“…Recent research on the island populations of Croatia revealed that the N1a lineage on the island of Cres is part of the European cluster of this ancestral lineage, which was previously thought to be present exclusively in the areas of Africa and Southeast Asia [66]. In the same study, a completely new subhaplogroup, HV2b, and subbranching of haplogroup X were discovered.…”
Section: Genetic Isolates Of Southeastern Europementioning
confidence: 84%
“…Recent research on the island populations of Croatia revealed that the N1a lineage on the island of Cres is part of the European cluster of this ancestral lineage, which was previously thought to be present exclusively in the areas of Africa and Southeast Asia [66]. In the same study, a completely new subhaplogroup, HV2b, and subbranching of haplogroup X were discovered.…”
Section: Genetic Isolates Of Southeastern Europementioning
confidence: 84%